ỨNG DỤNG CÔNG NGHỆ LỌC SINH HỌC TRONG HỆ THỐNG TUẦN HOÀN NƯỚC NUÔI GIỐNG CÁ BIỂN QUY MÔ SẢN XUẤT - Hiền, Nguyễn Thị Thu; Nhân, Trần Văn; Cự, Nguyễn Đức; Hương, Nguyễn Thị Thanh (Vietnam Journal of Science and Technology, 2012)
APPLICATIONS TECHNOLOGY RECIRCULATION AQUACULTURE SYSTEM BY SUBMERGED BIOFILTER AT COMMERCIAL MODEL Applications technology Recirculation Aquaculture System by Submerged Biofilter is orinentation for future development. The biological filter system were evaluated in 69 days rearing culture cobia (Rachycentron canadum) at the Ngoc Hai harchery, Do Son, Haiphong, a commercial scale research and demonstration recirculating aquaculture facility. Total ammoniacal nitrogen (TAN) removal rates were determined for this of biofilters for a range of concentrations ranging from 0.08 to 4.92 g TAN/m3/ngày. TAN concentrations were varied by feed rates, and limited by fish feeding response. Maximum feed rates were 0.71 kg/m3.day, using a 40% protein diet, total feeds was 23 kg/day. Average TAN removal rates (VTR) (in g TAN/m3.day of unexpanded media/day ± standard deviation, min – max) were 60.87 ± 99.8 (0.45, 424.53) g/m3.day this biofilter submerged. Nitrit remove rates (VNR) was 77.89 ± 125.86 (-19.97; 482.18) g/m3.day. These results are considerably lower than results previously published at the laboratory scale using artificial waste nutrients. This study highlights the need for future biofilter evaluations at the commercial scale using real aquaculture waste nutrients.